Passive Ankle-Foot Prosthesis Prototype with Extended Push-Off. (6th February 2013) - Brackx, Branko; Van Damme, Michaël; Matthys, Arnout; Vanderborght, Bram; Lefeber, Dirk
Current commercially available prosthetic feet have succeeded in decreasing the metabolic cost and increasing the speed of walking compared to walking with conventional, mostly solid prosthetic feet. However, there is still a large discrepancy when compared with a non-disabled gait, and the walking pattern remains strongly disturbed. During the stance phase of the leg, these prostheses store and return energy using a spring element. This spring returns to its neutral position, which generates a push-off, but the foot extends much less than with a non-disabled gait. The walking pattern may improve with a more extended push-off. In this paper, we present a passive ankle-foot prosthesis that aims to deliver an extended ankle push-off using a specific planetary gearbox arrangement and locking mechanisms in order to release the energy in the spring over the full natural stretching of the ankle. In recent years, both powered and passive prosthetic devices have been developed. The prosthetic foot presented in this paper is a passive system, such that it has the possibility to be made lighter and more robust than, for example, one driven by an electric motor. Preliminary walking experiments were conducted with a transfemoral amputee.